New physics, old metaphysics: quantum and quotidian in Ian McEwan's The Child in Time - Wright, Derek (Revista Alicantina de Estudios Ingleses, 1997)
This article investigates McEwan's poignant figurative use of ideas from the New Physics, his testing of their availability to quotidian reality, and determines to what extent and with what results—wonder, illusion, dementia, psychosis—the protagonist's behaviour is affected by a quantum mindset. An attempt is made to identify and define the kind of worldview and time-concept, physical or metaphysical, which is ultimately upheld by the novel's narrative structure and style, and to ascertain how far these are rooted in the Newtonian tradition of empirical realism which the book's theoretical discourse challenges. Time-reversal and parallel worlds theory are considered in the context of the novel's millenial-dystopian political vision.